Strategi Guru Aqidah Akhlak Dalam Mananamkan Karakter Peserta Didik Di Mi Wahid Hasyim - ats tsauri, Muhammad Sufyan; Andrean, Seka (Jurnal DIDIKA: Wahana Ilmiah Pendidikan Dasar, 2020)
Character is a basic value that builds one's person's person, formed both because of the influence of heredity and environmental influence, that distinguishes it from others, and is manifested by his attitudes and behaviors in daily life. In this case madrassas, especially the study of moral aqidah realized in islamic religious values to students. This research uses qualitative methods. Data collection is done with observations, interviews, and documentation. Data analysis is done by analyzing all the data from the results of the study, so that it can be used as a unit and then verified. The results showed that: (1) the learning planning of teacher Aqidah Akhlak as an effort to cultivate character is to design learning planning by involving media, (2) the application of teacher learning Aqidah Akhlak in an effort to plant the character of students that has been carried out in reference to the discipline and rules that have been planned and established in every learning activity or process in the basic educational institution.Keywords: Teacher Strategy, Character, Aqidah Akhlak Learning.Â